Powder containing specific boron nitride particles, heat dissipation sheet, and method for producing heat dissipation sheet

By using tubular boron nitride particles and block boron nitride particles with smaller crushing strength in the heat sink, combined with the pressurized molding process, the problem of thermal conductivity limitation in the prior art is solved, and more efficient heat dissipation is achieved performance.

CN119233942APending Publication Date: 2024-12-31DENKA CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280058440.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2021-08-31
Filing Date
2022-08-31
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The thermal conductivity of the existing hexagonal boron nitride powder in the heat sink is limited by the shape, size and strength of the block particles, making it difficult to effectively improve the thermal conductivity.

Method used

The heat sink is made by pressurized molding using powder containing tubular boron nitride particles and blocked boron nitride particles, and the long-side thermal conductivity and blocked boron nitride particles are used to utilize the long-side thermal conductivity of the tubular boron nitride particles and blocked boron nitride particles. The buffering effect improves thermal conductivity.

Benefits of technology

The thermal conductivity of the heat sink is significantly improved, forming a better heat transfer path, and enhancing the thermal conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119233942A_ABST
    Figure CN119233942A_ABST
Patent Text Reader

Abstract

A powder containing tubular boron nitride particles and bulk boron nitride particles that are aggregates of a plurality of primary boron nitride particles, the bulk boron nitride particles having a crushing strength of less than 7 MPa. A method for producing a heat sink, which comprises a step in which a composition containing tubular boron nitride particles, bulk boron nitride particles, which are aggregates of a plurality of primary boron nitride particles, and a resin, is molded into a sheet shape by pressurization, and wherein the crushing strength of the bulk boron nitride particles is less than 7 MPa. A heat sink which contains a tubular boron nitride particle, a plurality of boron nitride primary particles, and a resin, and in which a portion of the plurality of boron nitride primary particles is present within the tubular boron nitride particle.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a powder containing specific boron nitride particles, a heat sink, and a method for producing the heat sink. Background Art

[0002] In electronic parts such as power devices, transistors, thyristors, and CPUs, it is a challenge to efficiently dissipate the heat generated during use. To address this challenge, heat dissipation components containing ceramic powders with high thermal conductivity are used.

[0003] As a ceramic powder, boron nitride powder having properties such as high thermal conductivity, high insulation, and low relative dielectric constant has attracted attention. Boron nitride powder is usually composed of aggregated particles (blocky particles) formed by the aggregation of primary particles of boron nitride. For example, Patent Document 1 discloses a hexagonal boron nitride powder, which improves the filling property by further spheroidizing the shape of the aggregated particles, while achieving an increase in powder strength, and further, through high purification, achieves an increase in insulation and stabilization of withstand voltage of a heat transfer sheet filled with the powder.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2011-98882 Summary of the invention

[0007] Problems to be solved by the invention

[0008] When the hexagonal boron nitride powder described in Patent Document 1 is used, the thermal conductivity of the heat sink depends on the shape, size, strength, etc. of the bulk particles. In other words, if the shape, size, strength, etc. of the bulk particles are determined, the thermal conductivity of the heat sink using the bulk particles is also roughly determined, and there is a limit to improving the thermal conductivity of the heat sink by using a single hexagonal boron nitride powder.

[0009] Therefore, a main object of the present invention is to provide a boron nitride powder which can more effectively improve the thermal conductivity of a heat sink than a boron nitride powder consisting of a single bulk boron nitride particle.

[0010] Means for solving problems

[0011] One aspect of the present invention is a powder comprising tubular boron nitride particles and massive boron nitride particles which are aggregates of a plurality of boron nitride primary particles, wherein the crushing strength of the massive boron nitride particles is less than 7 MPa.

[0012] The inventors of the present application have conducted research and have found that if tubular boron nitride particles are used in addition to bulk boron nitride particles, the thermal conductivity of the heat sink can be expected to be improved. Furthermore, by using bulk boron nitride particles with a smaller crushing strength as the bulk boron nitride particles, the thermal conductivity of the heat sink can be more effectively improved.

[0013] In the above powder, the content of the tubular boron nitride particles may be 2 to 26 volume % based on the total volume of the powder.

[0014] In the above-mentioned powder, the tubular boron nitride particles may include boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.

[0015] In the above-mentioned powder, the strength of the tubular boron nitride particles can be 25 mN or more.

[0016] Another aspect of the present invention is a method for manufacturing a heat sink, which comprises a step of molding a composition containing tubular boron nitride particles, blocky boron nitride particles and a resin into a sheet by pressurizing, wherein the blocky boron nitride particles are aggregates of a plurality of boron nitride primary particles, and the crushing strength of the blocky boron nitride particles is less than 7 MPa.

[0017] Another aspect of the present invention is a heat sink comprising tubular boron nitride particles, a plurality of boron nitride primary particles, and a resin, wherein a portion of the plurality of boron nitride primary particles is present in the tubular boron nitride particles.

[0018] In the above heat sink, the orientation index may be 7-15.

[0019] In the above heat sink, the tubular boron nitride particles may include boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.

[0020] Effects of the Invention

[0021] According to the present invention, it is possible to provide a boron nitride powder capable of more effectively improving the thermal conductivity of a heat sink than a boron nitride powder consisting of a single type of bulk boron nitride particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] [ Figure 1 ] is a SEM image of the tubular boron nitride particles produced in Example 1.

[0023] [ Figure 2 ] is a SEM image of the cross section of the heat sink produced in Example 1.

[0024] [ Figure 3 ] is a SEM image of a cross section of the heat sink produced in Comparative Example 1. DETAILED DESCRIPTION

[0025] Hereinafter, embodiments of the present invention will be described in detail.

[0026] One embodiment of the present invention is a powder comprising: tubular boron nitride particles; and massive boron nitride particles that are aggregates of a plurality of boron nitride primary particles.

[0027] The tubular boron nitride particles have an elongated shape. The tubular boron nitride particles have: an outer shell formed of boron nitride; and a hollow portion surrounded by the outer shell. The hollow portion may be formed along the long side direction of the tubular boron nitride particles, or may be an elongated shape having a shape roughly similar to the appearance shape of the tubular boron nitride particles. At least one of the two ends in the long side direction of the tubular boron nitride particles is an open end and is connected to the hollow portion. Alternatively, both ends of the tubular boron nitride particles may be open ends.

[0028] The tubular boron nitride particles may be composed of a plurality of boron nitride sheets. The boron nitride sheets are formed of boron nitride and may have, for example, a scaly shape. In this case, the length of the long side direction of the boron nitride sheet may be, for example, greater than 1 μm or less than 10 μm. The plurality of boron nitride sheets constituting the tubular boron nitride particles may be in physical contact with each other or may be chemically bonded.

[0029] From the viewpoint of further improving the thermal conductivity of the heat sink, the maximum length of the tubular boron nitride particles may be 80 μm or more, 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, or 350 μm or more. The maximum length of the tubular boron nitride particles may be 1000 μm or less, 500 μm or less, 300 μm or less, or 250 μm or less.

[0030] The maximum length of the tubular boron nitride particles refers to the maximum length of the straight-line distance between any two points on one tubular boron nitride particle when the tubular boron nitride particles are observed with a scanning electron microscope (SEM). The maximum length can also be measured by importing the observed image (SEM image) of the tubular boron nitride particles into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.).

[0031] From the viewpoint of further improving the thermal conductivity of the heat sink, the aspect ratio of the tubular boron nitride particles may be 1.5 or more, 1.7 or more, 2.0 or more, 2.2 or more, 2.5 or more, 3.0 or more, 5.0 or more, or 7.0 or more. The aspect ratio of the tubular boron nitride particles may be 12.0 or less, 10.0 or less, 9.5 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.8 or less, or 2.6 or less.

[0032] The aspect ratio of the tubular boron nitride particle is defined as the maximum length (maximum length in the long side direction) L of the tubular boron nitride particle described above. A , and relative to the maximum length L A The maximum length (maximum length in the short side direction) of the tubular boron nitride particle in the direction perpendicular to the direction (long side direction) of B The ratio (L A / L B ). The maximum length L of the short side B The maximum length L in the long side direction can be used A The same method is used to measure.

[0033] The thickness of the outer shell of the tubular boron nitride particle may be 50 μm or less, 30 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less. From the viewpoint of easily maintaining the shape of the tubular boron nitride particle, the thickness of the outer shell may be 1 μm or more, 3 μm or more, or 5 μm or more. The thickness of the outer shell is defined as: when a straight line is drawn on the cross section of the tubular boron nitride particle in which the straight line distance between any two points becomes the largest, in an observation image (SEM image) when observing the cross section in a direction perpendicular to the long side direction of the tubular boron nitride particle by SEM, the average length of the portion of the straight line drawn on each outer shell.

[0034] The external shape of the tubular boron nitride particles may be columnar (rod-like), conical (conical, etc.), or bent. The tubular boron nitride particles may have a branching structure that branches in two or more directions.

[0035] From the viewpoint that the tubular boron nitride particles are less likely to collapse during the heat sink molding and the thermal conductivity of the heat sink is further improved, the strength of the tubular boron nitride particles can be more than 25mN, more than 26mN, more than 28mN, more than 30mN, more than 32mN, more than 35mN, more than 38mN, or more than 40mN. The strength of the tubular boron nitride particles can be less than 60mN, less than 55mN, less than 53mN, less than 50mN, less than 48mN, less than 45mN, or less than 42mN. The strength of the tubular boron nitride particles can be calculated by crushing 10 tubular boron nitride particles using a micro compression tester and according to the average value of the load size required for crushing. More specifically, first, more than 10 tubular boron nitride particles selected from the powder are arranged on a sample table. At this time, the tubular boron nitride particles are arranged in a manner such that the long side direction of each tubular boron nitride particle is along the setting surface of the sample table. Next, the indenter (e.g., indenter diameter of 200 μm) of a micro compression tester (e.g., manufactured by Shimadzu Corporation, MCT series) is lowered toward one tubular boron nitride particle on the sample stand, and a load is applied at a load rate of 0.27 mN / second. Then, the load size when the displacement in the short side direction of the tubular boron nitride particle rises sharply is measured as the size of the load required to crush the tubular boron nitride particle. The measurement is performed similarly for 10 tubular boron nitride particles, and the strength of the tubular boron nitride particles is calculated as the average value of the load sizes of the 10 tubular boron nitride particles.

[0036] The tubular boron nitride particles can be boron nitride particles (elastic boron nitride particles) that recover to a shape close to the original shape when unloading even if a load is applied from the outside. The fact that the tubular boron nitride particles are elastic boron nitride particles can be confirmed, for example, by the following method: when subjected to a load unloading test having a loading process and an unloading process in sequence, at least a portion of the length of the short side direction of the boron nitride particles compressed in the loading process is recovered in the unloading process, wherein the loading process is to compress the tubular boron nitride particles by gradually applying a load from 0.2 mN to 20 mN at a load speed of 0.27 mN / second in the short side direction, and the unloading process is to gradually unload to 0.2 mN at an unloading speed of 0.27 mN / second. It is believed that by making the tubular boron nitride particles elastic, it is easier to maintain a heat conduction path in the heat sink even if pressure and stress are applied to the tubular boron nitride particles, and therefore the tubular boron nitride particles are preferably elastic boron nitride particles.

[0037] Based on the total volume of the powder, the content of the tubular boron nitride particles can be 2% by volume or more, 4% by volume or more, 6% by volume or more, 8% by volume or more, or 10% by volume or more. Based on the total volume of the powder, the content of the tubular boron nitride particles can be 26% by volume or less, 24% by volume or less, 22% by volume or less, 20% by volume or less, 18% by volume or less, 16% by volume or less, 14% by volume or less, or 12% by volume or less. Based on the total volume of the powder, the content of the tubular boron nitride particles can be 2 to 26% by volume.

[0038] The tubular boron nitride particles can be obtained, for example, by forming boron nitride particles on a carbon sheet and recovering the boron nitride particles formed on the carbon sheet using the following production method, the production method comprising: a step of mixing 2 to 100 parts by mass of boric acid with 100 parts by mass of boron carbide powder having an average particle size of 5 to 100 μm to obtain a mixture; a step of filling the mixture into a graphite crucible; and a step of heating the covered graphite crucible in a resistance heating furnace for 3 to 40 hours under the conditions of 1450 to 2400° C. and 0.3 to 1.0 MPa in a nitrogen atmosphere while covering the opening of the graphite crucible with a carbon sheet and sandwiching the carbon sheet between the graphite crucible and the graphite crucible to fix the carbon sheet. The obtained tubular boron nitride particles can be appropriately crushed, sieved, washed, impurity removed, dried, etc.

[0039] The bulk boron nitride particles are aggregates of multiple boron nitride primary particles, and the multiple boron nitride primary particles can be physically in contact with each other. The boron nitride primary particles are formed of boron nitride and can have, for example, a scaly shape. In this case, the length of the long side direction of the boron nitride primary particles can be, for example, more than 1 μm, and can be less than 10 μm.

[0040] The average particle size of the bulk boron nitride particles can be 30 μm or more, 50 μm or more, 60 μm or more, 70 μm or more, or 80 μm or more. The average particle size of the bulk boron nitride particles can be, for example, 200 μm or less, 150 μm or less, 120 μm or less, 100 μm or less, 90 μm or less, 80 μm or less, 70 μm or less, 60 μm or less, 50 μm or less, or 40 μm or less. The average particle size of the bulk boron nitride particles is the d50 diameter in the volume-based particle size distribution, which can be measured using a laser diffraction particle size distribution measuring device.

[0041] The aspect ratio of the bulk boron nitride particles may be greater than 1.0, greater than 1.1, or greater than 1.2. The aspect ratio of the bulk boron nitride particles may be, for example, less than 5.0, less than 3.0, less than 2.0, or less than 1.5. The aspect ratio of the bulk boron nitride particles is defined as the maximum length (maximum length in the long side direction) L of the bulk boron nitride particles. C, and relative to the maximum length L C The maximum length of the blocky boron nitride particles in the direction perpendicular to the direction (long side direction) (maximum length in the short side direction) L D The ratio (L C / L D ). The maximum length L of the long side of the bulk boron nitride particle C And the maximum length L of the short side D The maximum length L in the long side direction of the tubular boron nitride particles can be used. A And the maximum length L of the short side B The same method is used to measure.

[0042] From the viewpoint of making it more difficult for the tubular boron nitride particles to collapse during the heat sink molding, the crushing strength of the bulk boron nitride particles can be less than 7 MPa, less than 6 MPa, less than 5 MPa, or less than 4 MPa. The crushing strength of the bulk boron nitride particles can be greater than 1 MPa, greater than 2 MPa, or greater than 3 MPa. The crushing strength of the bulk boron nitride particles refers to the average value of the crushing strength (also called particle strength, single particle crushing strength) of 10 bulk boron nitride particles measured in accordance with JIS R1639-5:2007. More specifically, the crushing strength (σ: unit MPa) of each bulk boron nitride particle is a dimensionless quantity (α=2.48: unitless) that varies according to the position within the particle, the crushing test force (P: unit N) and the particle size (d: unit μm), using the formula σ=α×P / (π×d 2 The crushing strength of the bulk boron nitride particles was calculated as the average value of the crushing strengths of 10 bulk boron nitride particles.

[0043] Based on the total volume of the powder, the content of the bulk boron nitride particles may be 74% by volume or more, 76% by volume or more, 78% by volume or more, 80% by volume or more, 82% by volume or more, 84% by volume or more, 86% by volume or more, 88% by volume or more, or 90% by volume or more. Based on the total volume of the powder, the content of the bulk boron nitride particles may be 98% by volume or less, 96% by volume or less, 94% by volume or less, 92% by volume or less, or 90% by volume or less.

[0044] The bulk boron nitride particles can be obtained, for example, by the following production method, which comprises: a step of nitriding boron carbide powder to obtain boron carbonitride powder; and a step of decarburizing the boron carbonitride powder to obtain bulk boron nitride particles. The obtained bulk boron nitride particles can be appropriately crushed, sieved, washed, impurity removed, dried, etc.

[0045] The tubular boron nitride particles and the bulk boron nitride particles may be composed substantially only of boron nitride. That the tubular boron nitride particles and the bulk boron nitride particles are composed substantially only of boron nitride can be confirmed by detecting only a peak derived from boron nitride in X-ray diffraction measurement.

[0046] The powder involved in one embodiment can more effectively improve the thermal conductivity of the heat sink by using tubular boron nitride particles and blocky boron nitride particles with smaller crushing strength, compared with the case of using tubular boron nitride particles and blocky boron nitride particles with larger crushing strength. As the reason, it is speculated as follows. It is believed that, first, the tubular boron nitride particles have an elongated shape, thereby making the thermal conductivity of the tubular boron nitride particles in the long side direction excellent. By using blocky boron nitride particles with smaller crushing strength, if the tubular boron nitride particles and blocky boron nitride particles are pressurized during the molding of the heat sink, the blocky boron nitride particles with smaller crushing strength are more likely to collapse than the tubular boron nitride particles. Therefore, the collapsed boron nitride primary particles play the role of a buffer material, thereby easily maintaining the shape of the tubular boron nitride particles even when pressure is applied to the tubular boron nitride particles. Therefore, it is speculated that a heat transfer path based on the tubular boron nitride particles is easily formed in the obtained heat sink, and the thermal conductivity is improved.

[0047] The powder according to one embodiment may contain other inorganic particles in addition to the tubular boron nitride particles and the bulk boron nitride particles. Examples of the other inorganic particles include boron nitride particles that are not tubular boron nitride particles and the bulk boron nitride particles, aluminum oxide particles, aluminum nitride particles, silicon carbide particles, and the like.

[0048] The powder containing the tubular boron nitride particles and the blocky boron nitride particles is used to prepare a composition mixed with a resin. In addition, the composition is formed into a sheet by pressurization, thereby obtaining a heat sink. That is, another embodiment of the present invention is a composition containing the above-mentioned tubular boron nitride particles, the above-mentioned blocky boron nitride particles, and a resin. In addition, another embodiment of the present invention is a method for manufacturing a heat sink, which comprises a step of forming a composition containing the above-mentioned tubular boron nitride particles, the above-mentioned blocky boron nitride particles, and a resin into a sheet by pressurization.

[0049] The resin may be, for example, a silicone resin, an epoxy resin, a silicone rubber, an acrylic resin, a phenolic resin, a melamine resin, a urea resin, an unsaturated polyester, a fluororesin, a polyimide, a polystyrene, a polyolefin, a polyamide, a polyamideimide, a polyetherimide, a polybutylene terephthalate, a polyethylene terephthalate, a polyphenylene ether, a polyphenylene sulfide, a wholly aromatic polyester, a polysulfone, a liquid crystal polymer, a polyethersulfone, a polycarbonate, a maleimide-modified resin, an ABS (acrylonitrile-butadiene-styrene) resin, an AAS (acrylonitrile-acrylic rubber·styrene) resin, or an AES (acrylonitrile·ethylene·propylene·diene rubber-styrene) resin.

[0050] The weight average molecular weight of the resin may be 1000 to 1000000 or 2000 to 800000. The weight average molecular weight of the resin may be measured by gel permeation chromatography (GPC) and measured in terms of polystyrene.

[0051] Based on the total volume of the composition, the resin content can be greater than 15 volume %, greater than 20 volume %, greater than 30 volume %, greater than 40 volume %, greater than 50 volume %, or greater than 60 volume %, and can be less than 80 volume %, less than 70 volume %, less than 60 volume %, less than 50 volume %, or less than 40 volume %.

[0052] Based on the total volume of the composition, the content of the tubular boron nitride particles in the composition may be 1 volume % or more, 2 volume % or more, 3 volume % or more, or 5 volume % or more, and may be 10 volume % or less, 9 volume % or less, 8 volume % or less, 7 volume % or less, 6 volume % or less, or 5 volume % or less.

[0053] Based on the total volume of the composition, the content of the bulk boron nitride particles in the composition can be greater than 40 volume %, greater than 42 volume %, greater than 43 volume %, or greater than 45 volume %, and can be less than 55 volume %, less than 54 volume %, less than 53 volume %, or less than 50 volume %.

[0054] Based on the total volume of the composition, the content of the above-mentioned powder in the composition can be more than 45 volume %, more than 46 volume %, more than 47 volume %, or more than 50 volume %, and can be less than 60 volume %, less than 58 volume %, less than 57 volume %, less than 55 volume %, less than 53 volume %, less than 51 volume %, or less than 50 volume %.

[0055] The composition may contain other components in addition to the resin, such as monomers, solvents, coupling agents, curing agents, curing accelerators (curing catalysts), wetting and dispersing agents, surface conditioners, addition reaction catalysts, organic particles, pigments, and the like.

[0056] Monomer can have polymerizable carbon-carbon double bond.Monomer can have acryloyl, methacryloyl, allyl, methallyl, vinyl, for example.As monomer, for example, can be acrylic acid, methacrylic acid, crotonic acid, 2-pentenoic acid, maleic acid, fumaric acid, itaconic acid, cinnamic acid, maleic acid monoalkyl ester, fumaric acid monoalkyl ester, maleic acid monocyclohexyl ester, fumaric acid monocyclohexyl ester, acrylate glycidyl, methacrylate glycidyl, allyl glycidyl ether, methallyl glycidyl ether, methyl acrylate, ethyl acrylate, butyl acrylate, 2-chloroethyl acrylate, methyl methacrylate, ethyl methacrylate, butyl methacrylate, 2-chloroethyl methacrylate, 2-chloroethyl vinyl ether, vinylbenzyl chloride, vinyl chloroacetate, allyl chloroacetate, diallyl fumarate.

[0057] Examples of the solvent include alcohol solvents, glycol ether solvents, aromatic solvents, and ketone solvents. Examples of the alcohol solvent include isopropyl alcohol and diacetone alcohol. Examples of the glycol ether solvent include ethyl cellosolve and butyl cellosolve. Examples of the aromatic solvent include toluene and xylene. Examples of the ketone solvent include methyl ethyl ketone and methyl isobutyl ketone.

[0058] The coupling agent can be a silane coupling agent. The silane coupling agent can have a reactive double bond, or can have a vinyl group, an allyl group, etc. As the silane coupling agent, allyl triethoxysilane, allyl chlorodimethylsilane, allyl trimethoxysilane, allyl trichlorosilane, chlorodimethyl vinyl silane, diethoxymethyl vinyl silane, dimethoxymethyl vinyl silane, trichlorovinyl silane, vinyl trimethoxy silane, dimethylethoxy vinyl silane, vinyl tris (2-methoxyethoxy) silane, etc. can be cited.

[0059] Examples of the curing agent include phenolic Novolac compounds, acid anhydrides, amino compounds, and imidazole compounds.

[0060] Examples of the curing accelerator (curing catalyst) include phosphorus-based curing accelerators such as tetraphenylphosphine tetraphenylborate and triphenylphosphate; imidazole-based curing accelerators such as 2-phenyl-4,5-dihydroxymethylimidazole; and amine-based curing accelerators such as boron trifluoride monoethylamine.

[0061] Examples of the wetting and dispersing agent include phosphate ester salts, carboxylic acid esters, polyesters, acrylic acid copolymers, and block copolymers.

[0062] Examples of the surface conditioner include acrylic surface conditioners, silicone surface conditioners, vinyl surface conditioners, and fluorine surface conditioners.

[0063] The composition can be prepared by mixing the above-mentioned powder and resin and other components as required by a known method (for example, mixing with a Henschel mixer).

[0064] In the process of molding the composition into a sheet by pressurizing (molding process), for example, the composition can be molded into a sheet by applying the composition to a substrate using a film applicator and pressurizing. In the molding process, the composition can be heated simultaneously with the pressurization of the composition. In the molding process, a process of curing a part or all of the resin in the composition can be performed simultaneously with or after molding (curing process).

[0065] From the viewpoint of collapsing the bulk boron nitride particles while maintaining the shape of the tubular boron nitride particles, the pressurization in the molding process can be carried out at a pressure of 7 MPa or more, 8 MPa or more, 10 MPa or more, or 12 MPa or less, or 16 MPa or less, 12 MPa or less, or 10 MPa or less.

[0066] When the composition contains a curable component (thermosetting or photocurable resin, monomer, etc.), the method for curing the resin in the composition can be appropriately selected according to the type of resin and / or monomer contained in the composition. For example, when the resin is an epoxy resin and the above-mentioned curing agent is used together, the resin can be cured by heating.

[0067] In the heat sink obtained in the above manner, when the composition is formed into a sheet, the massive boron nitride particles having a smaller crushing strength collapse preferentially over the tubular boron nitride particles, so that the boron nitride primary particles having collapsed massive boron nitride particles exist within the tubular boron nitride particles. That is, another embodiment of the present invention is a heat sink comprising tubular boron nitride particles, a plurality of boron nitride primary particles, and a resin.

[0068] The plurality of boron nitride primary particles are formed of boron nitride and may have, for example, a scaly shape. In this case, the length of the long side direction of the boron nitride primary particles may be, for example, 1 μm or more and 10 μm or less.

[0069] A portion of the plurality of boron nitride primary particles is present in the tubular boron nitride particles. In the heat sink, a portion of the plurality of boron nitride primary particles is present in the tubular boron nitride particles (in the hollow portion of the tubular boron nitride particles), which can be confirmed by observing the cross section of the heat sink using SEM. In the cross-sectional image (SEM image) of the heat sink, when the outer shell of the tubular boron nitride particles does not have an opening (forming a closed space), the inside of the tubular boron nitride particles refers to the inside of the closed space of the tubular boron nitride particles. In addition, in the cross-sectional image (SEM image) of the heat sink, when the outer shell of the tubular boron nitride particles has an opening, the inside of the tubular boron nitride particles refers to the straight line connecting the ends of the tubular boron nitride particles to each other at the opening, and the inner side of the portion surrounded by the outer shell of the tubular boron nitride particles. It should be noted that the straight line connecting the ends of the tubular boron nitride particles to each other at the opening is connected in a manner that the area of ​​the hollow portion of the tubular boron nitride particles becomes the largest.

[0070] The remnants of the plurality of boron nitride primary particles, i.e., the boron nitride primary particles other than the boron nitride primary particles in the tubular boron nitride particles (boron nitride primary particles outside the tubular boron nitride particles), are present throughout the entire heat sink. A portion of the boron nitride primary particles outside the tubular boron nitride particles may be in a bulk shape (a portion or all of the shape of the above-mentioned bulk boron nitride particles as a raw material may be maintained). In other words, the heat sink may contain bulk boron nitride particles that are aggregates of a plurality of boron nitride primary particles.

[0071] When the heat sink contains bulk boron nitride particles, it is difficult to confirm that the heat sink contains bulk boron nitride particles because it is difficult to distinguish the grain boundaries between the bulk boron nitride particles based on the observation image (SEM image) of the cross section of the heat sink. However, the fact that the heat sink contains bulk boron nitride particles can be confirmed using the following method.

[0072] First, the heat sink is placed on a ceramic boat and heated at 800°C for 2 hours in an electric furnace under the atmosphere to decompose and remove the components other than the boron nitride particles. Then, the particles remaining on the ceramic boat are observed using SEM. When the heat sink contains bulk boron nitride particles, the bulk boron nitride particles remain on the ceramic boat in a bulk state (a state that can be distinguished on the SEM image), so the presence of the bulk boron nitride particles (the heat sink contains bulk boron nitride particles) can be confirmed by the SEM image.

[0073] In the cross section of the heat sink, the area ratio of the hollow portion of the tubular boron nitride particles may be 40% or more, 50% or more, 60% or more, 70% or more, or 75% or more. The area ratio of the hollow portion of the tubular boron nitride particles may be 90% or less, 80% or less, or 75% or less. The area ratio of the hollow portion of the tubular boron nitride particles can be obtained by importing the cross-sectional image (SEM image) of the heat sink into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.), and calculating based on the cross-sectional image of the tubular boron nitride particles in the cross-sectional image.

[0074] From the viewpoint of further improving the thermal conductivity of the heat sink, the maximum length of the tubular boron nitride particles in the heat sink may be 80 μm or more, 100 μm or more, 125 μm or more, 150 μm or more, 175 μm or more, 200 μm or more, 225 μm or more, 250 μm or more, 300 μm or more, or 350 μm or more. The maximum length of the tubular boron nitride particles may be 1000 μm or less, 500 μm or less, 300 μm or less, or 250 μm or less.

[0075] The maximum length of the tubular boron nitride particles in the heat sink refers to the maximum length of the straight-line distance between any two points on one tubular boron nitride particle when the cross section of the heat sink is observed using a scanning electron microscope (SEM). The maximum length can be measured by importing the observed image (SEM image) of the cross section of the heat sink into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.).

[0076] From the viewpoint of further improving the thermal conductivity of the heat sink, the aspect ratio of the tubular boron nitride particles in the heat sink may be 1.5 or more, 1.7 or more, 2.0 or more, 2.2 or more, 2.5 or more, 3.0 or more, 5.0 or more, or 7.0 or more. The aspect ratio of the tubular boron nitride particles may be 12.0 or less, 10.0 or less, 9.5 or less, 9.0 or less, 8.0 or less, 7.0 or less, 6.0 or less, 5.0 or less, 4.0 or less, 3.0 or less, 2.8 or less, or 2.6 or less. The aspect ratio of the tubular boron nitride particles in the heat sink is defined in the same manner as the aspect ratio of the tubular boron nitride particles described above.

[0077] The thickness of the outer shell of the tubular boron nitride particles in the heat sink may be 50 μm or less, 30 μm or less, 15 μm or less, 10 μm or less, or 8 μm or less. The thickness of the outer shell may be 1 μm or more, 3 μm or more, or 5 μm or more. The thickness of the outer shell of the tubular boron nitride particles in the heat sink is defined as: when a straight line is drawn on the cross section of the tubular boron nitride particles in which the straight line distance between any two points becomes the largest in the observation image (SEM image) when the cross section of the heat sink is observed by SEM, the average length of the portion of the straight line drawn on each outer shell.

[0078] From the viewpoint of improving the thermal conductivity of the heat sink, the area ratio of the boron nitride particles (tubular boron nitride particles and boron nitride primary particles) in the heat sink can be 10% or more, 15% or more, or 20% or more. The area ratio of the boron nitride particles in the heat sink can be 90% or less, 80% or less, 70% or less, or 60% or less. The area ratio of the boron nitride particles in the heat sink is defined as: the cross-sectional images obtained by observing any 10 cross-sections of the heat sink at a magnification of 300 times using SEM are imported into image analysis software (for example, "Mac-view" manufactured by MOUNTECH Co., Ltd.), and the area ratio of the boron nitride particles (excluding the hollow part of the tubular boron nitride particles) in any 300μm×300μm area in each cross-sectional image is calculated, and the average value of the area ratios in the 10 cross-sectional images is calculated.

[0079] From the viewpoint of ease of manufacturing of the heat sink, the orientation index of the boron nitride particles in the heat sink may be 7 or more, 8 or more, 9 or more, 10 or more, or 11 or more. From the viewpoint of further improving the thermal conductivity in the thickness direction of the heat sink, the orientation index of the boron nitride particles in the heat sink may be 15 or less, 14 or less, 13 or less, or 12 or less. The orientation index may be 7 to 15. The orientation index can be calculated from the peak intensity ratio [I(002) / I(100)] of the (002) plane and the (100) plane of boron nitride measured by an X-ray diffraction device.

[0080] The type of resin in the heat sink is the same as the type of resin in the above-mentioned composition, and part or all of the resin in the heat sink may be cured. In other words, the heat sink may be a semi-cured (B stage) sheet in which part of the resin is cured, or a fully cured (C stage) sheet in which all of the resin is cured.

[0081] The area ratio occupied by the resin in the heat sink may be 10% or more, 20% or more, 30% or more, or 40% or more, and may be 90% or less, 85% or less, or 80% or less. The area ratio occupied by the resin in the heat sink is defined as: importing the cross-sectional images of any 10 cross-sectional views of the heat sink observed at a magnification of 300 times using SEM into image analysis software (e.g., "Mac-view" manufactured by MOUNTECH Co., Ltd.), calculating the area ratio occupied by the resin in any 300 μm×300 μm region in each cross-sectional image, and calculating the average value of the area ratios in the 10 cross-sectional views.

[0082] The thickness of the heat sink may be, for example, 50 μm or more, 80 μm or more, or 100 μm or less, and may be 1 mm or less, 800 μm or less, 500 μm or less, 400 μm or less, or 200 μm or less.

[0083] Example

[0084] Hereinafter, the present invention will be specifically described by way of examples, but the present invention is not limited to the following examples.

[0085] (Example 1)

[0086] [Manufacturing of tubular boron nitride particles]

[0087] 100 parts by mass of boron carbide powder with an average particle size of 10 μm and 9 parts by mass of boric acid were mixed and filled into a graphite crucible. The opening of the graphite crucible was covered with a carbon sheet (manufactured by NeoGraf), and the carbon sheet was clamped between the lid of the graphite crucible and the graphite crucible to fix the carbon sheet. The covered graphite crucible was heated in a resistance heating furnace at 2000°C and 0.85 MPa for 20 hours under a nitrogen atmosphere to generate tubular boron nitride particles on the carbon sheet. The SEM image of the boron nitride particles (tubular boron nitride particles) recovered from the carbon sheet is shown in Figure 1 The boron nitride particles recovered from the carbon sheet included tubular boron nitride particles having a maximum length of 200 μm and an aspect ratio of 2.5. The average strength of the load when 10 tubular boron nitride particles were crushed was 40 mN.

[0088] [Preparation of powder]

[0089] The produced tubular boron nitride particles and bulk boron nitride particles (crushing strength 4 MPa, average particle size 35 μm) were mixed at a volume ratio of 1:15 (= tubular boron nitride particles: bulk boron nitride particles) to prepare a powder.

[0090] [Manufacturing of heat sink]

[0091] 100 parts by mass of a naphthalene epoxy resin (HP4032 manufactured by DIC Corporation) and 10 parts by mass of an imidazole compound (2E4MZ-CN manufactured by Shikoku Chemical Co., Ltd.) as a curing agent were mixed, and then the prepared powders were further mixed to obtain a composition. In the obtained composition, the content of the tubular boron nitride particles was 3% by volume based on the total volume of the composition, and the content of the blocky boron nitride particles was 45% by volume based on the total volume of the composition.

[0092] The obtained composition was degassed at 500 Pa for 10 minutes and applied to a PET sheet to a thickness of 1.0 mm. 2 The pressing was performed under heating and pressing conditions for 60 minutes to produce a 0.5 mm heat sink.

[0093] The SEM image of the cross section of the manufactured heat sink is shown in Figure 2 In the cross section of the heat sink, it can be confirmed that part of the plurality of boron nitride primary particles exists in the tubular boron nitride particles. One tubular boron nitride particle ( Figure 2 In the figure, the maximum length of the tubular boron nitride particles indicated by arrows is 200 μm, the aspect ratio is 2.5, the area ratio of the hollow part in the boron nitride particles is 75%, and the thickness of the outer shell is 5 μm.

[0094] [Measurement of thermal conductivity]

[0095] A sample for measurement with a size of 10 mm × 10 mm was cut out from the produced heat sink, and the thermal diffusivity A (m 2 In addition, the specific gravity B (kg / m 3 ) was measured. In addition, the specific heat capacity C (J / (kg·K)) of the sample for measurement was measured using a differential scanning calorimeter (Rigaku Corporation, ThermoPlusEvo DSC8230). Using these physical property values, the thermal conductivity H1 (W / (m·K)) of the heat sink of Example 1 was calculated according to the formula H1=A×B×C.

[0096] It should be noted that, unlike the heat sink of Example 1, a heat sink in which tubular boron nitride particles are not used (the content of tubular boron nitride particles is 0 volume %) is prepared, and the thermal conductivity H0 of this heat sink is also measured in the same manner as above. Then, the ratio (H1 / H0) of the thermal conductivity H1 of the heat sink of Example 1 to the thermal conductivity H0 of the heat sink in which tubular boron nitride particles are not used is calculated. This ratio represents the degree of improvement (increase ratio) of the thermal conductivity of the heat sink brought about by the use of tubular boron nitride. The results are shown in Table 1.

[0097] [Determination of Orientation Index]

[0098] For the heat sink of the embodiment, in order to confirm the state of the boron nitride in the heat sink, an X-ray diffraction device (manufactured by Rigaku Co., Ltd., trade name: ULTIMA-IV) was used to determine the orientation index [I(002) / I(100)] of the boron nitride in the heat sink. The heat sink placed on the sample holder of the X-ray diffraction device was irradiated with X-rays and baseline correction was performed. Then, the peak intensity ratio of the (002) plane to the (100) plane of the boron nitride was calculated. This was recorded as the orientation index [I(002) / I(100)]. The orientation index of the heat sink of Example 1 was 11.13.

[0099] (Example 2)

[0100] The powder was prepared by changing the volume ratio of tubular boron nitride particles to blocky boron nitride particles to 1:9, and the content of tubular boron nitride particles in the composition was 5% by volume based on the total volume of the composition. The same operations as in Example 1 were performed to prepare a heat sink, measure thermal conductivity, and measure orientation index. It should be noted that in the measurement of thermal conductivity, the thermal conductivity of the heat sink of Example 2 was set to H1, and the thermal conductivity of the heat sink of Example 2 without using tubular boron nitride particles (the content of tubular boron nitride particles was 0% by volume) was set to H0. The orientation index of the heat sink of Example 2 was 9.49.

[0101] (Comparative Example 1)

[0102] The heat sink was prepared and the thermal conductivity was measured in the same manner as in Example 2 except that the bulk boron nitride particles (average particle size 85 μm) with a crushing strength of 7 MPa were used. The SEM image of the cross section of the prepared heat sink is shown in FIG. Figure 3 It should be noted that in the measurement of thermal conductivity, the thermal conductivity of the heat sink of Comparative Example 1 was set to H1, and the thermal conductivity of the heat sink of Comparative Example 1 without using tubular boron nitride particles (the content of tubular boron nitride particles was 0 volume %) was set to H0.

[0103] (Comparative Example 2)

[0104] As the bulk boron nitride particles, bulk boron nitride particles (average particle size 42 μm) having a crushing strength of 11 MPa were used. Except for this, the heat sink was prepared and the thermal conductivity was measured in the same manner as in Example 2. It should be noted that in the measurement of the thermal conductivity, the thermal conductivity of the heat sink of Comparative Example 2 was set to H1, and the thermal conductivity of the heat sink of Comparative Example 2 in which the tubular boron nitride particles were not used (the content of the tubular boron nitride particles was 0 volume %) was set to H0.

[0105] [Table 1]

[0106]

Claims

1. A powder containing: Tubular boron nitride particles; and The bulk boron nitride particles are aggregates of multiple boron nitride primary particles. The crushing strength of the blocky boron nitride particles is less than 7 MPa.

2. The powder according to claim 1, wherein Based on the total volume of the powder, the content of the tubular boron nitride particles is 2 to 26 volume %.

3. The powder according to claim 1 or 2, wherein The tubular boron nitride particles include boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.

4. The powder according to any one of claims 1 to 3, wherein The strength of the tubular boron nitride particles is greater than 25 mN.

5. A method for producing a heat sink, comprising the step of molding a composition containing tubular boron nitride particles, blocky boron nitride particles and a resin into a sheet by pressurizing, wherein the blocky boron nitride particles are aggregates of a plurality of boron nitride primary particles. The crushing strength of the blocky boron nitride particles is less than 7 MPa.

6. A heat sink comprising: Tubular boron nitride particles; a plurality of boron nitride primary particles; and Resin, A portion of the plurality of boron nitride primary particles is present in the tubular boron nitride particles.

7. The heat sink according to claim 6, which has an orientation index of 7 to 15.

8. The heat sink according to claim 6 or 7, wherein: The tubular boron nitride particles include boron nitride particles having a maximum length of 80 μm or more and an aspect ratio of 1.5 or more.